Relationship of biofilm formation and different virulence genes in uropathogenic Escherichia coli isolates from Northwest Iran - Fattahi, Sargol; Kafil, Hossein Samadi; Nahai, Mohammad Reza; Asgharzadeh, Mohammad; Nori, Roghaya; Aghazadeh, Mohammad (German Medical Science GMS Publishing House, 2015)
Background and objectives: The () bacterium is one of the main causative agents of urinary tract infections (UTI) worldwide. The ability of this bacterium to form biofilms on medical devices such as catheters plays an important role in the development of UTI. The aim of the present study was to investigate the possible relationship between virulence factors and biofilm formation of isolates responsible for urinary tract infection.Materials and methods: A total of 100 isolates isolated from patients with UTI were collected and characterized by routine bacteriological methods. In vitro biofilm formation by these isolates was determined using the 96-well microtiter-plate test, and the presence of , , and virulence genes was examined by PCR assay. Data analysis was performed using SPSS 16.0 software.Results: From 100 isolates isolated from UTIs, 92% were shown to be biofilm positive. The genes , , and were detected in 43%, 94% and 26% of isolates, respectively. Biofilm formation in isolates that expressed , , and genes was 100%, 93%, and 100%, respectively. A significant relationship was found between presence of the gene and biofilm formation in isolates isolated from UTI (<0.01), but there was no statistically significant correlation between presence of and genes with biofilm formation (<0.072, <0.104). Conclusion: Results showed that and genes do not seem to be necessary or sufficient for the production of biofilm in , but the presence of correlates with increased biofilm formation of urinary tract isolates. Overall, the presence of , , and virulence genes coincides with in vitro biofilm formation in uropathogenic